Application of Quercus salicina extract in the management of urolithiasis - Lu, Pei; Pu, Junyan; Zong, Yiping; Wang, Zijie; Han, Peng; Gu, Min (Frontiers in Medicine, 2022)
Since 1969，a herbal medicine extracted from Quercus salicina Blume/Quercus stenophylla Makino (QS), has been clinically used for the management of urolithiasis in Japan. Historically, the decoction of leaves and shoots of QS trees was popularly utilized as folk prescription to remove urinary calculi. This study was designed to perform a brief review about the updated progress of QS extract for urinary stones based on previous studies. Comprehensive literature search was conducted in multiple electronic databases including Web of Science, PubMed and EMBASE, and relevant data on QS extract were extracted. As a result, the major mechanism of QS extract for urolithiasis is observed to be closely related with the anti-oxidative activities according to recent studies, leading to inhibition the accumulation of renal calcium and prevention of stone formation and recurrence of stones. As for the effect of discharging stones, loosening upper urinary tract has also been noticed recently. More extensive studies are still necessary to systemically evaluate the individual dosage, drug safety and targeted stone types.